Astra and Bessarabian church (Confluenţe Bibliologice, 2012)
In this article the author mentions the contribution of Bessarabian Romanian scholars in the establishment of ASTRA (Transilvanian Association for Romanian Literature and the Culture of Romanian People), the role and prodigious work of the bishops Visarion Puiu, Balti-Hotin Diocese and Dimitrie Erhan, the Diocese of Ismail White Fortress, church contribution side by side with the ASTRA to improve cultural-artistic life of Bessarabia interwar.
Keywords: history of Bessarabia